The Innovation of Teaching Mode of Machine Tool Electrical Control in Technical Colleges - Lin, Xianchang (Journal of Theory and Practice of Contemporary Education, 2023)
With the deepening reform of the education and teaching system, as the cradle of the training of complex skilled personnel in machine tool electrical control, technical colleges and universities should adhere to the basic principle of keeping pace with the times, innovate teaching models, strengthen comprehensive quality, transport high-quality skilled personnel for the society, and promote the sustainable development of electrical engineering.